Antithrombotic activity of protein S infused without activated protein C in a baboon thrombosis model - Heeb, Mary J.; Marzec, Ulla; Gruber, Andras; Hanson, Stephen R. (Thrombosis and Haemostasis, 2012)
Protein S (ProS) is an essential plasma protein that enhances the anticoagulant activity of activated protein C (APC). In vitro, purified native human Zn2+-containing ProS also exerts direct anticoagulant activity by inhibiting prothrombinase and extrinsic FXase activities independently of APC. We investigated antithrombotic effects of ProS infused without APC in a baboon shunt model of thrombogenesis that employs a device consisting of arterial and venous shear flow segments. In in vitro experiments, the Zn2+-containing human ProS used for the studies displayed >10-fold higher prothrombinase inhibitory activity and anticoagulant activity in tissue factor-stimulated plasma, and four-fold higher inhibition of the intrinsic pathway than the Zn2+-deficient ProS used. In the thrombosis model, ProS (33 μg/minute for 1 hour) or saline was infused locally; platelet and fibrin deposition in the shunt were measured over 2 hours. During experiments performed at 50 ml/minute blood flow, Zn2+-containing ProS inhibited platelet deposition 73–96% in arterialtype flow segments and 90–99% in venous-type flow segments; Zn2+-deficient ProS inhibited platelet deposition 52% in arterial-type flow segments and 65–73% in venous-type flow segments. At 100 ml/min blood flow rate, Zn2+-containing ProS inhibited platelet deposition by 39% and 73% in the respective segments; Zn2+-deficient ProS inhibited platelet deposition by 5% and 0% in the respective segments. Zn2+-containing ProS suppressed fibrin deposition by 67–90%. Systemic APC-independent ProS activity was significantly increased and thrombin-antithrombin complex levels were significantly decreased after infusion of ProS. Thus, infused human Zn2+-containing ProS is antithrombotic in primates, and may have therapeutic potential even in protein C-deficient human patients.These studies were presented in part in abstract form at an oral presentation at the XXIth Congress of the International Society on Thrombosis and Haemo -stasis, Geneva, Switzerland, August 2007.
Keywords: Anticoagulants; platelets; protein S; thrombosis model